IL-22 Protects Against Liver Pathology and Lethality of an Experimental Blood-Stage Malaria Infection - Mastelic, Béatris (Frontiers Research Foundation, 2012)
The host response following malaria infection depends on a fine balance between levels of pro-inflammatory and anti-inflammatory mediators resulting in the resolution of the infection or immune-mediated pathology. Whilst other components of the innate immune system contribute to the pro-inflammatory milieu, T cells play a major role. For blood-stage malaria, CD4(+) and γδ T cells are major producers of the IFN-γ that controls parasitemia, however, a role for TH17 cells secreting IL-17A and other cytokines, including IL-17F and IL-22 has not yet been investigated in malaria. TH17 cells have been shown to play a role in some protozoan infections, but they also are a source of pro-inflammatory cytokines known to be involved in protection or pathogenicity of infections. In the present study, we have investigated whether IL-17A and IL-22 are induced during a Plasmodium chabaudi infection in mice, and whether these cytokines contribute to either protection or to pathology induced during the infection. Although small numbers of IL-17- and IL-22-producing CD4 T cells are induced in the spleens of infected mice, a more pronounced induction is observed in the liver, where increases in mRNA for IL-17A and, to a lesser extent, IL-22 were observed and CD8(+) T cells, rather than CD4 T cells, are a major source of these cytokines in this organ. Although the lack of IL-17 did not affect the outcome of infection or pathology, lack of IL-22 resulted in 50% mortality within 12 days after infection with significantly greater weight loss at the peak of infection and significant increase in alanine transaminase in the plasma in the acute infection. As parasitemias and temperature were similar in IL-22 KO and wild-type control mice, our observations support the idea that IL-22 but not IL-17 provides protection from the potentially lethal effects of liver damage during a primary P. chabaudi infection.